Worlding and provincialising smart cities: From individual case studies to a global comparative research agenda. (February 2021) - Miller, Byron; Ward, Kevin; Burns, Ryan; Fast, Victoria; Levenda, Anthony
The diversity of smart city case studies presented in this special issue demonstrates the need for provincialised understandings of smart cities that account for cities' worlding strategies. Case studies drawn from North America, South America, Europe, the Middle East and Asia show that 'the smart city' takes very diverse forms, serves very diverse objectives, and is embedded in complex power geometries that vary from city to city. Case studies are a critical strategy for understanding phenomena in context, yet they present their own epistemological and ontological limitations. We argue for a more-than-Global-North smart city research agenda focused on the comparative analysis of smart cities, an agenda that foregrounds the conjunctural geographies of relationships and processes shaping these cities.